Biological Aging Predicts Vulnerability to COVID-19 Severity in UK Biobank Participants - Kuo, Chia-Ling (J Gerontol A Biol Sci Med Sci, 2021)
BACKGROUND: Age and disease prevalence are the 2 biggest risk factors for Coronavirus disease 2019 (COVID-19) symptom severity and death. We therefore hypothesized that increased biological age, beyond chronological age, may be driving disease-related trends in COVID-19 severity. METHODS: Using the UK Biobank England data, we tested whether a biological age estimate (PhenoAge) measured more than a decade prior to the COVID-19 pandemic was predictive of 2 COVID-19 severity outcomes (inpatient test positivity and COVID-19-related mortality with inpatient test-confirmed COVID-19). Logistic regression models were used with adjustment for age at the pandemic, sex, ethnicity, baseline assessment centers, and preexisting diseases/conditions. RESULTS: Six hundred and thirteen participants tested positive at inpatient settings between March 16 and April 27, 2020, 154 of whom succumbed to COVID-19. PhenoAge was associated with increased risks of inpatient test positivity and COVID-19-related mortality (OR(Mortality) = 1.63 per 5 years, 95% CI: 1.43–1.86, p = 4.7 × 10(−13)) adjusting for demographics including age at the pandemic. Further adjustment for preexisting diseases/conditions at baseline (OR(M) = 1.50, 95% CI: 1.30–1.73 per 5 years, p = 3.1 × 10(−8)) and at the early pandemic (OR(M) = 1.21, 95% CI: 1.04–1.40 per 5 years, p = .011) decreased the association. CONCLUSIONS: PhenoAge measured in 2006–2010 was associated with COVID-19 severity outcomes more than 10 years later. These associations were partly accounted for by prevalent chronic diseases proximate to COVID-19 infection. Overall, our results suggest that aging biomarkers, like PhenoAge may capture long-term vulnerability to diseases like COVID-19, even before the accumulation of age-related comorbid conditions.